The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.846290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autonomy Support and Emotion Regulation on Teacher Burnout in the Era of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has exacerbated levels of stress and anxiety for P-12 teachers around the globe. The present study aims to understand teachers’ emotional experiences and feelings of burnout during the pandemic, and how individual (i.e., emotion regulation strategies) or contextual factors (e.g., school administrative support) intersect with different facets of their emotional experiences. Using a sequential explanatory mixed methods design, we collected and examined survey and interview data from teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 80 publications
(135 reference statements)
0
12
0
Order By: Relevance
“…A more complex view, which considers both individual teacher and school contextual aspects of their well-being at school, received more attention recently, considering that some sociodemographic aspects may also play an important role [ 52 ]. It is possible to consider that self-care is both individual and community.…”
Section: Discussionmentioning
confidence: 99%
“…A more complex view, which considers both individual teacher and school contextual aspects of their well-being at school, received more attention recently, considering that some sociodemographic aspects may also play an important role [ 52 ]. It is possible to consider that self-care is both individual and community.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, social support – from school leadership, colleagues, or in the private environment – is also considered highly relevant ( Sokal et al, 2020b ; Jakubowski and Sitko-Dominik, 2021 ; Kim et al, 2022 ). For example, teachers who experience their school leadership as autonomy-supportive report less burnout and emotional exhaustion ( Collie, 2021 ; Chang et al, 2022 ). Further research should examine which type of social support is helpful for teachers during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, social support -from school leadership, colleagues, or in the private environment -is also considered highly relevant (Sokal et al, 2020b;Jakubowski and Sitko-Dominik, 2021;Kim et al, 2022). For example, teachers who experience their school leadership as autonomy-supportive report less burnout and emotional exhaustion (Collie, 2021;Chang et al, 2022) (Voss and Kunter, 2020). Accordingly, the exchange of materials and literature seems to be of greater relevance in how prospective teachers experience emotional exhaustion than is the emotional support of peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to tackle thwarting of teachers' competence, responses from American high school teachers have highlighted necessary administrative support in several areas, such as providing tools and related professional development, counseling, support, tips, and resources, including those which can improve the interactions among teachers, students and parents ( 32 ). In terms of autonomy, several studies have reported the impact of lack of administrative support on reduced work autonomy among teachers ( 33 ) while advocating for specific administrative actions to enhance autonomy, including clear curriculum guidelines for online teaching, provision of appropriate online platforms, scheduling of “self-care” time during the day, surveying of teachers to assess their needs, and expressing interest in teachers' input. In terms of relatedness, administrative support is a protective factor in terms of burnout, with emotional support, monitoring, provision of mental health to promote self-care, support for parent-teacher communication, and top-down guidance critical to the prevention of relatedness thwarting ( 34 ).…”
Section: Introductionmentioning
confidence: 99%